PERENCANAAN KEBUTUHAN RUANG PARKIR DI KAWASAN TAMAN SARI KOTA BANDA ACEH - Nur Wahida; Renni Anggraini; Muhammad Isya (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Parking lot is a necessity for vehicles owner who whant their vehicle parking at the place that is easy to reach, one of which is parking on the road. Parking on the road can cause decreased in road capacity, delayed traffic flow, and the use of the road becomes ineffective. High land prices become a problem for urban areas, which indirectly impact on parking arrangements. Off street parking is highly efficient parking applied in a place with high level activity. Road segment of  Tgk. Abdullah Ujong Rimba and Tgk. Abu Lam U which located in the center of the old town in taman Sari area, do not have parking on street parking facilities.  The existence of green open area (Taman Sari) which is the center of the city and often used for religious, festival, exhibition, local tourists tours, culutural, politics and other activites, are not supported with adequate parking area (off street parking), so the visitors parking in the street (on-street parking). This research is planning parking area needs for parking facility in the form of parking building. From the results of analysis and parking building facility design, which refers to Planning Guideliness and The operation of Parking facilities issued by (Director General of Land Transportation) in 1998, known that the needs of parking space in green open area and offices area (Taman Sari) is 543 unit of parking space ( 348 unit of parking space four-wheeled and195 unit of parking space  two-wheeled).the result is 2 Floor Parking building design with 880 unit of parking space (360 unit of parking space four-wheeled and 520 two-wheeled. (337 unit of parking space is Surplus (12 unit of parking space four-wheeled and 325 unit of parking space  two-wheeled).